Pre-exercise health screening in the UAE: A necessity or barrier to engage in physical activity? - Rifah Anwar Assadi; Afreen Abdul Rahim Sanaullah; Sathyapriya Nandagopal; Shahnaz Mohamed Wazil; Priya Pardasani; Meenadarsini Dhamothiran; And Ozyigit; Jagat Gopinath; Ans Ahmed Mahmood; Maryam Almarzooqi; Bibi Morsal Sayedy; Elham Riyaz; et al. (PLoS ONE, 2025)
Background Sedentary lifestyles contribute to the rise of non-communicable diseases, making physical activity (PA) crucial for public health. Pre-exercise screening is an important tool for ensuring safety, but its utilization and the factors influencing its adoption need further exploration. Objective This study assesses the utilization of pre-exercise screening among physical activity facility users in the UAE, identifying sociodemographic and health-related factors associated with screening practices. Methods A cross-sectional study was conducted among adults aged 18 and above in the UAE. Data were collected through a self-administered questionnaire from 630 adults using PA facilities, covering socio-demographic characteristics, PA engagement, knowledge of PA benefits, and pre-exercise screening practices. Data analysis was performed using SPSS version 28 for descriptive and inferential statistics. Results Of the participants, 496 (78.7%) were unemployed, 554 (87.6%) were aged 18–34, 294 (46.7%) had bachelor’s degrees, and 522 (82.9%) were single. Females made up 52% of the respondents. Only 186 (29.5%) underwent pre-exercise screening, with 377 (59.8%) not screened and 67 (10.6%) uncertain. Associations were found between higher screening utilization and factors such as being over 30 years old (44.9%), male (33.9%), having higher education (33.5%), and being employed (40.3%). Participants with chronic health conditions, including heart disease (52.4%), chest pain (48%), and mental health problems (50%), were significantly more likely to utilize pre-exercise screening (P < 0.001). The purpose of pre-exercise screening as risk stratification was recognized by 214 (34.1%), while 257 (40.7%) understood its preventive role. Using the 2023 PARQ + , 401 (63.7%) were cleared for PA, and 229 (36.3%) required further evaluation due to medical or mental health issues. Most participants (83.4%) did not receive guidance from exercise professionals, but 74.3% favoured mandatory pre-exercise screening. Conclusions The study highlights a gap in pre-exercise screening utilization in the UAE, with significant associations to sociodemographic factors and health conditions. The findings highlight the need for increased awareness and adoption of pre-exercise screening in the UAE. Addressing knowledge gaps and implementing mandatory screening protocols could improve health literacy and safety in PA facilities.